Faktor – Faktor Yang Mempengaruhi Terhadap Produktivitas Kerja Karyawan Pada Proyek MEP PT. Mediacipta Perkasa Mandiri - Unggul Prasetyo; Yanthy Herawaty (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to determine how much influence the variables of Compensation, Competence, Occupational Health and Safety (K3) have on employee work productivity at PT Mediacipta Perkasa Mandiri. The population in this study were 82 employees. This study used a saturated sample, which means that all 82 employees were sampled. This study uses SPSS to answer the main facts by using a list of questionnaires distributed and answered by respondents. In this study, compensation has a positive and significant effect on employee work productivity at PT Mediacipta Perkasa Mandiri, competence does not have a positive and significant effect on employee work productivity at PT. Mediacipta Perkasa Mandiri and Occupational Safety and Health have no positive or significant effect on employee work productivity at PT Mediacipta Perkasa Mandiri